The Cost of Conducting a 24-Hour Dietary Recall Using INDDEX24, a Mobile Dietary Assessment Platform, Compared to Pen-and-Paper in Viet Nam and Burkina Faso. (7th June 2021) - Adams, Katherine; Bell, Winnie; Somé, Jérôme; Colaiezzi, Brooke; Wafa, Sarah; Rogers, Beatrice; Coates, Jennifer
Abstract: Objectives: Dietary data are rarely collected in low- and middle-income countries due to complexity, cost, and time burden. To facilitate the collection and use of individual dietary data, the International Dietary Data Expansion (INDDEX) Project has developed INDDEX24, a novel dietary assessment platform to collect and analyze 24-hr dietary recall (24HR) data. This study assessed the cost and cost-efficiency (cost per respondent) of INDDEX24 compared to the traditional pen-and-paper interview (PAPI) approach to collecting and processing 24HR data. Methods: Conducted alongside validation studies of the INDDEX24 platform in Viet Nam and Burkina Faso, we carried out activity-based costing studies to estimate and compare the cost of using INDDEX24 and PAPI to conduct a 24HR survey. We defined and costed a series of activities required to complete data collection and prepare the datasets, including development of dietary reference data, survey preparation, training, survey execution, data entry, and data cleaning and processing. Results: In Viet Nam, the total economic cost of the 24HR was $111, 004 ($755/respondent, n = 147) using INDDEX24 and $120, 483 ($820/respondent, n = 147) using the PAPI modality. In Burkina Faso, the total cost of the 24HR using INDDEX24 was $78, 043 ($538/respondent, n = 145) and $78, 933 ($541/respondent, n = 146) using PAPI. The higher costs in Viet Nam were primarily driven by the preparation of dietary reference data, which was an extensive and nationally focused effort, whereas in Burkina it was regionally focused and benefited from previous development of relevant dietary data. In both countries, while INDDEX24 had higher costs associated with survey preparation (including purchasing tablets and a CommCare subscription), these costs were more than offset by the higher PAPI costs associated with data entry and data cleaning and processing. Conclusions: In two distinct contexts, the cost of conducting a 24HR was lower (Viet Nam) or approximately equivalent (Burkina Faso) using INDDEX24 than using PAPI. As the INDDEX24 dietary reference database is populated with reference data from which future users of INDDEX24 can draw, the cost of using INDDEX24 will likely decline further. Funding Sources: The INDDEX Project is implemented by the Tufts University Friedman School of Nutrition Science and Policy with funding from The Bill & Melinda Gates Foundation.